'They Put a Few Coins in Your Hand to Drop a Baby in You': A Study of Peacekeeper-fathered Children in Haiti. Issue 2 (14th March 2020) - Lee, Sabine; Bartels, Susan
ABSTRACT: Many peace support operations have faced allegations of sexual exploitation and abuse perpetrated by UN personnel against members of local communities. Some of these intimate relations result in children being born but there is little empirical data on the experiences of women and girls who conceive and bear these children. We analyse 265 self interpreted narratives from community members in Haiti about children fathered by UN personnel and born to local women or girls. The mixed methods results highlight three important themes: (a) poverty is a key underlying factor contributing to sexual exploitation and abuse by peacekeeping personnel, (b) the repatriation of implicated peacekeepers often leaves the woman and child in exacerbated poverty, and (c) intimate relations with fair-skinned peacekeepers and having fair-skinned children are sometimes perceived as desirable. The data highlight that children fathered by MINUSTAH personnel are typically being raised in settings of extreme economic deprivation and are often denied access to education and other basic services that would enable them to break the cycle of poverty. While the overarching need identified in this analysis is financial, additional research with the children themselves in warranted to identify other needs and to inform policies and programmes intended to improve their well-being.